2002
DOI: 10.1542/peds.110.3.e34
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Risperidone for the Treatment of Disruptive Behavior Disorders in Children With Subaverage IQs

Abstract: ABSTRACT. Objective. The objective of this study was to investigate the long-term safety and efficacy of risperidone in disruptive behavior disorders in children with subaverage IQs. Disruptive behavior disorders were defined as oppositional defiant disorder, disruptive behavior disorder, and conduct disorder as per the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) criteria.Methods. This was a 48-week open-label (OL) extension study of risperidone in 77 children diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(127 citation statements)
references
References 41 publications
7
117
2
1
Order By: Relevance
“…There is initial evidence in the form of open-label or retrospective chart review studies, of the efficacy of olanzapine, quetiapine, and aripiprazole in treating aggressive behavior [663]. Risperidone was found to be well-tolerated and superior to placebo in reducing aggressive behaviors in children with CD [664-666]. Two large controlled trials found risperidone to be superior to placebo in ameliorating hostile and aggressive behavior in lower-functioning children with disruptive behavioral disorders [667,668].…”
Section: Reviewmentioning
confidence: 99%
“…There is initial evidence in the form of open-label or retrospective chart review studies, of the efficacy of olanzapine, quetiapine, and aripiprazole in treating aggressive behavior [663]. Risperidone was found to be well-tolerated and superior to placebo in reducing aggressive behaviors in children with CD [664-666]. Two large controlled trials found risperidone to be superior to placebo in ameliorating hostile and aggressive behavior in lower-functioning children with disruptive behavioral disorders [667,668].…”
Section: Reviewmentioning
confidence: 99%
“…Weight gain was more significant in the first month of treatment, with a deceleration over time, as expected. 31,32 As the more pronounced weight gain was observed within 1 month, it can mostly be attributed to drug effect and not to normal physical development. Although weight gain lessens with long-term use of risperidone, it is still a risk factor for many health problems, such as heart disease, hypertension, dyslipidemia and diabetes, and should be closely monitored.…”
Section: Pharmacogenetics Of Risperidone In Autismmentioning
confidence: 99%
“…A number of studies suggest efficacy and relative safety of risperidone for a host of psychiatric problems in children and adolescents, including tic disorders (Gilbert et al, 2004;Scahill et al, 2003), the psychotic symptoms of schizophrenia (Zalsman et al, 2003), and disruptive behavior in children with low IQ (Turgay et al, 2002) or with pervasive developmental disorders, such as autism (Masi et al, 2003;McCracken et al, 2002). Similar evidence exists for the efficacy of olanzapine in treating disorders in adolescents such as bipolar disorder (Frazier et al, 2001) and schizophrenia (Findling et al, 2003).…”
Section: False Positivesmentioning
confidence: 99%